Makran Coastal Zoning for the Construction of New Marine Areas based on Hydrological and Hydraulic Characteristics Using Satellite Data and Spatial Analysis - Khanzadi, Hossein; Vakilabadi, Karim Akbari; Almasi, Ramin (Sustainable Marine Structures, 2020)
On one hand, the diversity of activities and on the other hand, the conflicts between beneficiaries necessitate the efficient management and supervision of coastal areas. Accordingly, monitoring and evaluation of such areas can be considered as a critical factor in the national development and directorship of the sources. With regard to this fact, remote sourcing technologies with use of analytical operations of geographic information systems (GIS), will be remarkably advantageous. Iran’s south-eastern Makran coasts are geopolitically and economically, of importance due to their strategic characteristics but have been neglected and their development and transit infrastructure are significantly beyond the international standards. Therefore, in this paper, with regard to the importance of developing Makran coasts, a Multi-Criterion Decision Analysis (MCDA) method was applied to identify and prioritize the intended criteria and parameters of zoning, in order to establish new maritime zones. The major scope of this study is to employ the satellite data, remote sensing methods, and regional statistics obtained from Jask synoptic station and investigate the region’s status in terms of topography, rainfall rate and temperature changes to reach to a comprehensive monitoring and zoning of the coastal line and to provide a pervasive local data base via use of GIS and MCDA, which will be implemented to construct the coastal regions.In this article, while explaining the steps of coastal monitoring, its main objectives are also explained and the necessary procedures for doing so are presented. Then, the general steps of marine climate identification and study of marine parameters are stated and the final achievements of the coastal monitoring process are determined. In the following, considering that this article focuses on the monitoring of Makran beaches, the method of work in the mentioned region will be described and its specific differences and complexities will be discussed in detail. Also, the impact of such projects on future research results will be discussed. ER